EDITORIAL (American Journal of Islam and Society, 1991)
This issue, like all the previous ones, opens with ‘AbdulHamid AbQSulaymsn’s“Guiding Light.” But this time we have given it a subtitle andwould like to invite our readers’ attention to the important issue addressedhere. AbiiSulaymSin quotes the Qur’an and the hadith to show that the constitutionalprocess of political authority and government in Islam isshiirii -decision making through consultation. The individual is required toparticipate seriously in the shuratic process and enjoin what is good andoppose what is evil through peaceful means. The Qur’an, AbQSulaymh asserts,requires patience and peaceful struggle in the face of internal oppression anddissension, but authorizes the oppressed to fight and use force against outsideaggression and occupation. Internally, force and violence have no placein solving political issues within the ummah. We hope that the author’s conclusionwill initiate a discussion, and we encourage our readers to respond.This is followed by Louay M. Safi‘s article on the purpose of an Islamicstate, its source of political legitimacy, and the scope of state power. He arguesthat a clear distinction should be made between the role and purpose of thestate and those of the ummah. Only through such a separation of objectives,writes Safi, we can properly observe the injunctions of the Shari‘ah and theprinciples of revelation.An Islamic state, according to Safi, should be identified with the systemof rules determining the quality of life in the political organs necessary forthe realization of Islamic ideals. Such an entity naturally presupposes a societycommitted to Islamic principles and norms.Eric A. Winkel deals with the paradigm shifts in political science inthe postmodern debate. Beginning with Kuhn’s belief that paradigm shiftsare mainly passive and the natural result of people realizing that the presentprevalent paradigm contains some anomalies, a belief which he does not share,Winkel goes on to show how that paradigm supports the ruling elite. Thisline is continued in his analysis of the views of Ashley and Gilpin, who arerepresentatives of opposing viewpoints. Taking the modern Western paradigm,which is built on a scientific worldview and self-interest, he shows how thisconstruct has been used to propagate the idea that the West has reached thepinnacle of civilization due to its scientific superiority vis-‘a-vis the rest ofthe world. He then looks at what the West has done with its advancement:genetic engineering (in effect changing reality to suit its desires), relegating ...